THE EXTRACTION OF NATURAL DYES FROM JACKFRUIT WOOD WASTE (Artocarpus Heterophyllus Lamk) WITH WATER SOLVENT BY USING THE MICROWAVE METHOD (Universitas Negeri Semarang, 2018)
Currently, exploration of natural dyes is increasingly being activated and developed, especially to find natural sources of dyes from different plant species and also to develop natural dyestuff extraction process technology for textile applications. During this natural dye extraction process is done by conventional methods that require a long time and a large amount of solvent. Therefore, it is a necessary alternative to the use of